Assessment of Morphological Variation of Malaysian Halodule Species Complex - Ahmad Nazri, Norhapizah (2007)
Halodule uninervis and H. pinifolia are widely distributed along the southwest, south and east coast of Peninsular Malaysia, Sabah and Sarawak. Eleven locations were selected for this study and each site has different habitat characteristics. Samplings and collections of Halodule plants were conducted from August 2002 until May 2004. From the study Halodule species occurred on various habitats and a variety of substrates; sand, coralline sand, coral degraded sand, loamy sand, calcareous sandy-mud, sandy-mud, mud and soft mud. They also grow in wide range of salinity (18-34‰) and depths (-1.5 to -7.0 m MSL). These species were found growing as a single pure population or exist in association with other seagrasses (e.g. H. pinifolia, H. ovalis, H. minor, H. spinulosa, Halophila species, C. rotundata, C. serrulata, T. hemprichii and E. acoroides), seaweeds (e.g. Ulva reticulata, Acanthophora spicifera and Gracillaris sp.) and fauna (e.g. fishes, echinodermata, cnidaria, mollusca and crustacea). Halodule uninervis and H. pinifolia have the capability to adapt in different environments through changes in morphology. Plants on exposed site have short leaves with short erect stems while plants that are under shade and always in submerge condition have long leaves with long erect stems. In addition plants from an area of high sedimentation also have long erect stems. Branching erect stems with roots at the nodes were found where the substrate is loose coralline sand. Results also showed that plants growing on substrate that contain mud tend to have wider leaves compared to plants on sand substrate. Studies found the types of substrate and spaces availability for the growth of plants have an affect on the morphological variation of rhizome internodes for both species. Leaf sheath morphology, pattern of leaf surfaces, and anatomical structures were not affected by habitat characteristics for both H. uninervis and H. pinifolia. Laboratory culture studies on H. uninervis in different conditions, showed changes in morphological characteristics. The plants showed similar decrement in length of leaves (almost 50%) for different conditions (with cultures kept under the same amount of ambient light) suggest that light influence the leaf length characteristics. The leaves tend to be narrow for plants in natural substrate (3%) compared to artificial substrate (50%) suggesting that substrate types influenced the leaf width characteristics. Leaf tip morphology did not change among cultures. Culture observation on H. pinifolia in laboratory condition showed that leaves tend to be narrow throughout the period of the study. Observation found that the leaf tip morphology of H. pinifolia changes under laboratory conditions. Halodule pinifolia exhibited the leaf tip morphology that belongs to H. uninervis.